2011
DOI: 10.1016/j.ajhg.2011.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Recent Admixture in an Indian Population of African Ancestry

Abstract: Identification and study of genetic variation in recently admixed populations not only provides insight into historical population events but also is a powerful approach for mapping disease loci. We studied a population (OG-W-IP) that is of African-Indian origin and has resided in the western part of India for 500 years; members of this population are believed to be descendants of the Bantu-speaking population of Africa. We have carried out this study by using a set of 18,534 autosomal markers common between I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…Thus, efficient mapping of disease-causing variants are improved if the divergence between the ancestral populations is large. A large difference in the prevalence of the disease between the ancestral and derived populations adds to the successfully mapping of disease-causing variants, which is more often observed in the case of the admixed populations [85]. A study on the Indian populations spanning African descendants has shown the importance of admixture in mapping the diseases [85].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, efficient mapping of disease-causing variants are improved if the divergence between the ancestral populations is large. A large difference in the prevalence of the disease between the ancestral and derived populations adds to the successfully mapping of disease-causing variants, which is more often observed in the case of the admixed populations [85]. A study on the Indian populations spanning African descendants has shown the importance of admixture in mapping the diseases [85].…”
Section: Reviewmentioning
confidence: 99%
“…A large difference in the prevalence of the disease between the ancestral and derived populations adds to the successfully mapping of disease-causing variants, which is more often observed in the case of the admixed populations [85]. A study on the Indian populations spanning African descendants has shown the importance of admixture in mapping the diseases [85]. A significant enrichment of processes related to ion-channel activity and cadherin genes was found.…”
Section: Reviewmentioning
confidence: 99%
“…Although there have been many population genetic studies based on genotyping array data (Xing et al 2009; Reich et al 2009; Narang et al 2011; Moorjani et al 2013; Basu et al 2016), there is a scarcity of publicly available whole genome sequence data from the Indian subcontinent. The Phase 3 1000 Genomes Project (KGP) data provides a great resource for studying Indian genomic variation based on whole genome sequence (WGS) data, as it includes five populations from the Indian subcontinent (Auton et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several genetic studies have suggested that they are most closely related to Africans (Gauniyal et al 2008, 2011) and have traced their ancestry to Bantu language speakers from subSaharan Africa (Narang et al 2011; Shah et al 2011). The Bantu populations refer to 300–600 African ethnic groups, who speak Bantu languages belonging to the Bantoid subgroup of Benue-Congo branch in the Niger-Congo language family and predominantly occupy western-central, eastern and southern Africa (Butt 2006; Nurse 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Given the extensive and intricate nature of population expansions that spanned across Africa the precise geographic deduction of the ancestral origin of Siddi genomes had so far remained elusive (Narang et al 2011). In the present study we sought to map the biogeographical origin of the Indian Siddi groups using the GPS algorithm.…”
Section: Discussionmentioning
confidence: 99%